A nurse-led clinic for patients consulting with osteoarthritis in general practice: development and impact of training in a cluster randomised controlled trial. Issue 1 (December 2016) - Healey, Emma; Main, Chris; Ryan, Sarah; McHugh, Gretl; Porcheret, Mark; Finney, Andrew; Morden, Andrew; Dziedzic, Krysia
Abstract Background Despite a lack of service provision for people with osteoarthritis (OA), each year 1 in 5 of the general population consults a GP about a musculoskeletal condition such as OA. Consequently this may provide an opportunity for practice nurses to take an active role in helping patients manage their condition. A nurse led clinic for supporting patients with OA was developed for the MOSAICS study investigating how to implement the NICE 2014 OA Guideline core recommendations. This paper has two main objectives, firstly to provide an overview of the nurse-led OA clinic, and secondly to describe the development, key learning objectives, content and impact of the training to support its delivery. Methods A training programme was developed and delivered to provide practice nurses with the knowledge and skill set needed to run the nurse-led OA clinic. The impact of the training programme on knowledge, confidence and OA management was evaluated using case report forms and pre and post training questionnaires. Results The pre-training questionnaire identified a gap between what practice nurses feel they can do and what they should be doing in line with NICE OA guidelines. Evaluation of the training suggests that it enabled practice nurses to feel more knowledgeable and confident in supporting patients to manage their OA and this was reflected in the clinical management patients received in the nurse-led OA clinics. Conclusions A significant gap between what is recommended and what practice nurses feel they can currently provide in terms of OA management was evident. The development of a nurse training programme goes some way to develop a system in primary care for delivering the core recommendations by NICE. Trial registration The cluster trial linked to this training was conducted from May 2012 through February 2014 by the Arthritis Research UK Primary Care Centre, Keele University, UK (Trial registration numberISRCTN06984617 ).